Sikap Pemertahanan Bahasa Jawa pada Masyarakat Desa G2 Dwijaya Kecamatan Tugumulyo Kabupaten Musi Rawas - Syaiful Abid; Nur Nisai Muslihah; Lesy Puspitasari (LP4MK STKIP PGRI Lubuklinggau, 2018)
The objective of this research was to describe the attitude of Javanese language retention in the community of G2 Dwijaya Village, Tugumulyo Subdistrict, Musi Rawas District in the realm of adolescents and adults. The research method uses a qualitative descriptive method. The subjects of this research were 180 children, adolescents, and adults. Data collection techniques were carried out using questionnaire techniques. The collected data is then analyzed according to the steps of data analysis, starting with scoring, interpretation, and making conclusions. From the results of data analysis, it is known that the attitude of Javanese language retention from adolescents with an average value is 89.38 with a very good category, and for adolescents with an average value of 88.97 with very good categories. Thus, the attitude of Javanese language retention to the people of G2 Dwijaya Village, Tugumulyo District, Musi Rawas Regency reached an average value of 89.18 with a very good Javanese language defense attitude category.